Carbon Nanodots for All-in-One Photocatalytic Hydrogen Generation - Jana, Bikash; Reva, Yana; Scharl, Tobias; Strauss, Volker; Cadranel, Alejandro; Guldi, Dirk Michael (Journal of the American Chemical Society, 2021)
Carbon nanodots (CNDs) were photochemically altered to produce dihydrogen under light irradiation. Within the complex structure of CNDs, photo-oxidation takes place at citrazinic acid molecular fluorophore sites. Important is the fact that the resulting CND materials have a dual function. On one hand, they absorb light, and on the other hand, they photo- and electrocatalytically produce dihydrogen from water and seawater, without any external photosensitizer or cocatalyst. Record HER activities of 15.15 and 19.70 mmol(H2) g(catalyst)-1 h-1 were obtained after 1 h of 75 mW/cm2 Xe lamp illumination, from water and seawater, respectively. This impressive performance outweighs the remaining structural uncertainties. A full-fledged physicochemical investigation based on an arsenal of steady-state and time-resolved spectroscopic characterizations together with microscopy enabled a comprehensive look into the reaction mechanism. For an efficient dihydrogen formation, a precatalytic activation by means of reduction with a sacrificial electron donor is imperative.
CRIS-Team Scopus Importer:2021-12-24